A Lung Adenocarcinoma Patient With a Rare EGFR E709_T710delinsD Mutation Showed a Good Response to Afatinib Treatment: A Case Report and Literature Review - Wei, Yu; Cui, Yueli; Guo, Yao; Li, Lei; Zeng, Liang (Frontiers in Oncology, 2021)
For advanced lung adenocarcinoma patients with common epidermal growth factor receptor (EGFR) mutations (exon 19 deletions or the exon 21 L858R mutation), tyrosine kinase inhibitors (TKIs) are the standard therapies, and achieve favorable responses. However, for the rare EGFR deletion-insertion mutation of exon 18, there is no evidence of the efficacy of EGFR TKIs. Herein, we report a lung adenocarcinoma patient harboring a rare EGFR E709_T710delinsD mutation who was treated with afatinib as the first-line therapy and achieved a progression-free survival of 23 months. After the disease progressed, the patient received almonertinib treatment and exhibited a stable disease. This case indicated that non-small cell lung cancer patients harboring the EGFR E709_T710delinsD mutation could benefit from afatinib treatment, followed with almonertinib treatment, as a potential therapeutic strategy.